EVALUASI KEWIRAUSAHAAN PETANI DALAM RANGKA PENGEMBANGAN OLAHAN PISANG DI DESA BANDUNG KECAMATAN PLAYEN KABUPATEN GUNUNGKIDUL (EVALUATION OF FARMERS ENTREPRENEURSHIP IN ORDER TO DEVELOP ON BANANA PROCESSING AT BANDUNG VILLAGE, PLAYEN SUB DISTRICT, GUNUNGKI - Iswardayati, Nani Tri; Yulianto, Gunawan; Munanto, Totok Sevenek (Jurnal Ilmu-Ilmu Pertanian, 2013)
This study aimed to: 1) determine the level of personality farmers, farmers' level of ability in dealing with others, the level of skill set, the ability of farmers in marketing, the ability of farmers about the money, 2) to determine the profile of entrepreneurship acumen as an entrepreneur farmers, 3) to find ways to develop entrepreneurial farmers. By using a descriptive analysis of the information obtained entrepreneurial personality farmer level reached 248.8 or at the level of 69%, the level of ability to relate to others in the entrepreneurial reached 252.275 or at the level of 70.2%, the level of entrepreneurial skill set to reach a value of 226 or at rate of 62.7%, in terms of marketing reached 217 or at the level of 60.3%, in terms of money reached 198.2 or at the level of 55.05%. Assessment of all aspects of entrepreneurship described that farmers entrepreneurial acumen and farmers entrepreneurial ingenuity in the research area reached a level of 63.45%. Intelligence farmers were also described with advantages in terms of: 1) responsible for the work, 2) discipline on completion of the work and 3) excelence in communicating with others, and there is a weakness in terms of: 1) leadership, 2) marketing and 3) money.